Mesoscale imaging with cryo‐light and X‐rays: Larger than molecular machines, smaller than a cell. (14th November 2016) - Ekman, Axel A.; Chen, Jian‐Hua; Guo, Jessica; McDermott, Gerry; Le Gros, Mark A.; Larabell, Carolyn A.
Abstract : Review : Within a cell, molecules self‐organise to create mesoscale structures. The mesoscale ranges from the size of the molecular machines up to that of an individual cell and includes key structures such as mitochondria, lipid drops and the nucleus. Soft X‐ray tomography is an excellent method for visualising and quantifying mesoscale organisation, particularly when used in conjunction with fluorescence microscopy. Correlation of these two types of data generates a high‐resolution reconstruction of the cell, annotated with the locations of specific molecules. Abstract : In the context of cell biology, the term mesoscale describes length scales ranging from that of an individual cell, down to the size of the molecular machines. In this spatial regime, small building blocks self‐organise to form large, functional structures. A comprehensive set of rules governing mesoscale self‐organisation has not been established, making the prediction of many cell behaviours difficult, if not impossible. Our knowledge of mesoscale biology comes from experimental data, in particular, imaging. Here, we explore the application of soft X‐ray tomography (SXT) to imaging the mesoscale, and describe the structural insights this technology can generate. We also discuss how SXT imaging is complemented by the addition of correlative fluorescence data measured from the same cell. This combination of two discrete imaging modalities produces a 3D view of the cell that blends high‐resolution structural information with precise molecular localisation data.